TECHNOLOGY FOR PLANNING THE MANUFACTURING PROCESS OF GUIDE VANES IN FRANCIS TURBINE HYDROELECTRIC POWER PLANTS - Mauludin, Wandi; Hatta, Achmad (Jurnal Rekayasa Mesin, 2025)
PT XYZ is a company engaged in manufacturing, one of the products made is a Guide Vane for Hydroelectric Power Plants. The production process is carried out based on the terms of reference that has been made. The terms of reference do not have detailed information about the work steps, so that production activities are fully charged to the machine operator which has the potential for process errors and workpiece results. The way to improve the manufacturing process is to create process planning documentation, with the aim of simplifying the work process and calculating cost estimates. Documentation is made using the EMCO process planning method. Process planning is done on CNC milling machines and lathes. The results of the process planning made resulted in four processes with a total time of 2422,68 minutes. The process time obtained results in an estimated production cost of making a directional blade of Rp. 17.753.473,37 per piece.